As armas e as letras inglesas : a instrução militar e o ensino de inglês na corte do Rio de Janeiro (1810-1832) - José, Elisson Souza de São (2015)
This Dissertation has as its objective a study of the teaching of English in military training, especially in the Military Academy of the court of Rio de Janeiro. The work has the timeframe from 1810 to 1832. The year 1810 was chosen as the starting point because on December 4th, the Royal Military Academy was created by King John VI, expressed in the Charter Act. It contained all the fundamental aspects for the proper functioning of the Academy, which included the teaching of English, French or German, where the military junta thought necessary. But the final milestone of the research was established in 1832, because it was the year in which, there was a change in the military status and the teaching of foreign languages is no longer required. The Dissertation, at first, will address the issues that led the Portuguese to take an interest in learning the English language. In a second step, it will address the importance of modern languages - English and French - for the training of military, since the military books and some of the Portuguese army officers were foreigners. Finally, the text will address some aspects of the teaching career of Eduardo Thomaz Colville, first and only English teacher of the Royal Military Academy of the researched period. The results obtained from the research was that the English language, together with the French, was essential for understanding of military books that were in foreign languages, therefore without this knowledge, the soldiers would be unable to perform their duties and receive promotions. In the construction of the dissertation were used various scientific character of works, such as books, theses, dissertations, papers, articles, manuscripts and journals.